Taylor series a. Use the definition of a Taylor series to find the first four nonzero terms of the Taylor series for the given function centered at a. b. Write the power series using summation notation. f(x)=2^x,a=1

snowlovelydayM 2021-01-19 Answered
Taylor series
a. Use the definition of a Taylor series to find the first four nonzero terms of the Taylor series for the given function centered at a.
b. Write the power series using summation notation.
\(f(x)=2^x,a=1\)

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Expert Answer

pierretteA
Answered 2021-01-20 Author has 25006 answers
Given :
The function is \(f(x)=2^x\) and center at a=1
The definition of a Taylor series :
\(\sum_{k=0}^\infty c_k(x-a)^k,\text{ where }c_k=\frac{f^k(a)}{k!},\text{ for }k=0,1,2,3,...\)
a)To use the definition of a Taylor series to find the first four nonzero terms of the Taylor series for the given function centered at a
Find derivative of the function .
\(f(x)=2^x\)
\(f'(x)=2^x\ln(2)\)
\(f''(x)=2^x\ln^2(2)\)
\(f'''(x)=2^x\ln^3(2)\)
\(f^4(x)=2^x\ln^4(2)\)
To find derivative f(x) at x=1
\(f(1)=2\)
\(f'(1)=2\ln(2)\)
\(f''(1)=2\ln^2(2)\)
\(f'''(1)=2\ln^3(2)\)
\(f^4(1)=2\ln^4(2)\)
To find the first four nonzero terms of the Taylor series .
\(c_0=f(1)=2,c_1=\frac{f'(1)}{1!}=\frac{2\ln(2)}{1!},c_2=\frac{f''(1)}{2!}=\frac{2\ln^2(2)}{2!},c_3=\frac{f'''(1)}{3!}=\frac{2\ln^3(2)}{3!},c_4=\frac{f^4(1)}{4!}=\frac{2\ln^4(2)}{4!}\)
The in general \(c_k=\frac{2\ln^k(2)}{k!}\)
b) To write the power series using summation notation .
By using definition of a Taylor series and part a.
The series for centered at a=1 is
\(\sum_{k=0}^\infty c_k(x-a)^k=\sum_{k=0}^\infty\frac{2\ln^k(2)}{k!}(x-1)^k\)
Not exactly what you’re looking for?
Ask My Question
34
 
content_user
Answered 2021-12-17 Author has 11055 answers

Answer is given below (on video)

0

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Relevant Questions

asked 2021-03-11
Taylor series and interval of convergence
a. Use the definition of a Taylor/Maclaurin series to find the first four nonzero terms of the Taylor series for the given function centered at a.
b. Write the power series using summation notation.
c. Determine the interval of convergence of the series.
\(f(x)=\log_3(x+1),a=0\)
asked 2021-01-02
Write out the first three nonzero terms of the Taylor series for the following functions centered at the given point a. Then write the series using summation notation.
\(f(x)=\tan^{-1}4x,a=0\)
asked 2020-12-29
Taylor series Write out the first three nonzero terms of the Taylor series for the following functions centered at the given point a. Then write the series using summation notation.
\(\displaystyle{f{{\left({x}\right)}}}={\text{cosh}{{\left({2}{x}-{2}\right)}}},{a}={1}\)
asked 2021-11-03
Find a power series for the function, centered at c, and determine the interval of convergence.
\(\displaystyle{g{{\left({x}\right)}}}=\frac{{3}}{{2}}{x}-{1},{c}={2}\)
asked 2020-11-22
Any method
a. Use any analytical method to find the first four nonzero terms of the Taylor series centered at 0 for the following functions. You do not need to use the definition of the Taylor series coefficients.
\(f(x)=x^2\cos x^2\)
asked 2021-03-07

Working with binomial series Use properties of power series, substitution, and factoring to find the first four nonzero terms of the Maclaurin series for the following functions. Use the Maclaurin series
\((1+x)^{-2}=1-2x+3x^2-4x^3+\cdots\ for\ -1\)
\((1+4x)^{-2}\)

asked 2021-11-02

Solve the given differential equation by means of a power series about the given point x0. Find the first four nonzero terms in each of two linearly independent solutions (unless the series terminates sooner). If possible, find the general term in each solution.

\((a) y''-xy'-y = 0, x_0 = 0\)

\((b) y''-xy'-y = 0, x_0 = 1\)

\((c) (2+4x-2x^2)y'-12(x-1)y'-12y = 0, x_0 = 1\)

\((d) e^x-y''+ln(1+x)y'-xy = 0, x_0 = 0\)

...